Impact of biofilms in drinking water contamination by Escherichia coli coliform - Anabela Borges (2015)
Waterborne diseases continue to be an important cause of illness and death with particular incidence in developing countries. Indeed, the use of contaminated drinking water (DW) has been linked with several health problems worldwide. So, the main goal of water companies is to ensure that water is microbiologically and chemically safe for consumers. Many of the problems in DW distribution systems (DWDS) are microbiological and thus the prevention of water associated problems has mainly focused on these contaminations. There are several public health relevant microorganisms that may be transmitted through contaminated DW and infect humans. Even more worrying is the fact that waterborne bacterial pathogens have the potential to become components of sessile microbial communities. Biofilms can act as environmental reservoirs of coliforms (intestinal and non-intestinal origin) and other clinically relevant pathogens, representing a potential source of water contamination. The presence of biofilms in DWDS constitutes special concern because they provide the ideal environment for pathogens to survive and persist for long time in distribution networks. As biofilms are recalcitrant to treatment, they also contribute to the reduced efficiency of disinfection programs. This chapter provides an overview about the involvement of biofilms in waterborne diseases. In addition, the impact of the presence of biofilms in DWDS and on the organoleptic quality of the distributed water will be also discussed. As Escherichia coli is an indicator of fecal contamination and some of their variants, enterotoxigenic and enterohemorrhagic, are one of the major causes of water-related outbreaks, their role will be also highlighted.